Screening for mutations in two exons of FANCG gene in Pakistani population - Aymun, Ujala; Iram, Saima; Aftab, Iram; Khaliq, Saba; Nadir, Ali; Nisar, Ahmed; Mohsin, Shahida (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
BACKGROUND: Fanconi anemia is a rare autosomal recessive disorder of genetic instability. It is both molecularly and clinically, a heterogeneous disorder. Its incidence is 1 in 129,000 births and relatively high in some ethnic groups. Sixteen genes have been identified among them mutations in FANCG gene are most common after FANCA and FANCC gene mutations. OBJECTIVE: To study mutations in exon 3 and 4 of FANCG gene in Pakistani population. METHODS: Thirty five patients with positive Diepoxybutane test were included in the study. DNA was extracted and amplified for exons 3 and 4. Thereafter Sequencing was done and analyzed for the presence of mutations. RESULTS: No mutation was detected in exon 3 whereas a carrier of known mutation c.307+1 G>T was found in exon 4 of the FANCG gene. CONCLUSION: Absence of any mutation in exon 3 and only one heterozygous mutation in exon 4 of FANCG gene points to a different spectrum of FA gene pool in Pakistan that needs extensive research in this area.
Keywords: Pakistan; exony; surveillance populace; Humans; protein FANCG; Fanconi Anemia Complementation Group A Protein; Female; mutace; Exons; FANCG gene; lidé; protein FANCA; ženské pohlaví; Fanconi Anemia Complementation Group G Protein; Male; Mass Screening; Pákistán; diepoxybutane test; Population Surveillance; Fanconi anemia; plošný screening; Mutation; mužské pohlaví; screening for mutation